Ethnocultural regionalization of Lithuania or all the truth about our regions - Ragauskaitė, Alma (Acta Museologica Lithuanica, 2019)
In a broad sense the subject of this research is the territorial organization of Lithuania’s ethnocultural regions. In a narrow sense it focuses on Lithuania’s ethnocultural regions. This research aims to carry out ethnocultural regionalization of Lithuania.More in PDF.You can purchase a printed book:www.patogupirkti.ltwww.knygos.lt
Keywords: none